2019
DOI: 10.1111/ppl.12891
|View full text |Cite
|
Sign up to set email alerts
|

Warming and water deficit impact leaf photosynthesis and decrease forage quality and digestibility of a C4 tropical grass

Abstract: Global warming is predicted to cause more intense extreme events such as heat waves, flooding and severe droughts, producing significant effects on agriculture. In tropics, climate change will severely impact livestock production affecting water availability, forage quality and food for cattle. We investigated the isolated and combined effects of soil water deficit (wS) and + 2°C increase in canopy temperature (eT) on leaf gas exchange, chlorophyll fluorescence, carbohydrate content, forage quality and in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 88 publications
(125 reference statements)
5
42
0
3
Order By: Relevance
“…The content of CP, ADF (16.26%-55.39%), NDF, EE (2.48%-4.38%), Ash (7.89%-21.95%) and WSC (3.08%-6.76%) in this study were equivalent to the results (CP: 2.71%-19.21%; ADF: 9.06%-48.30%; NDF: 12.16%-76.23%; EE: 0.64%-10.90%; Ash: 3.49%-12.47%; WSC: 1.24%-17.27%) observed in alpine meadows on the Tibetan Plateau by previous studies (Xu et al, 2002;Shi et al, 2013;Sun et al, 2015;Zhang et al, 2015b;Fan et al, 2017;Li and Liu, 2017;Zhang et al, 2017;Li et al, 2018). Increased water availability may have increased the content of CP in this study, which was in line with the results observed in the steppes of Inner Mongolia Autonomous Region, China (Schönbach et al, 2012;Ren et al, 2016a), a C4 tropical grass in Brazil (Habermann et al, 2019), mountain side grasslands in North-West Greece (Roukos et al, 2011) and alpine meadows on the Tibetan Plateau (Yao et al, 2019). This finding may be related to several mechanisms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The content of CP, ADF (16.26%-55.39%), NDF, EE (2.48%-4.38%), Ash (7.89%-21.95%) and WSC (3.08%-6.76%) in this study were equivalent to the results (CP: 2.71%-19.21%; ADF: 9.06%-48.30%; NDF: 12.16%-76.23%; EE: 0.64%-10.90%; Ash: 3.49%-12.47%; WSC: 1.24%-17.27%) observed in alpine meadows on the Tibetan Plateau by previous studies (Xu et al, 2002;Shi et al, 2013;Sun et al, 2015;Zhang et al, 2015b;Fan et al, 2017;Li and Liu, 2017;Zhang et al, 2017;Li et al, 2018). Increased water availability may have increased the content of CP in this study, which was in line with the results observed in the steppes of Inner Mongolia Autonomous Region, China (Schönbach et al, 2012;Ren et al, 2016a), a C4 tropical grass in Brazil (Habermann et al, 2019), mountain side grasslands in North-West Greece (Roukos et al, 2011) and alpine meadows on the Tibetan Plateau (Yao et al, 2019). This finding may be related to several mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…First, increased water availability may accelerate soil nitrogen mineralization and in turn increase the availability of nitrogen to plants (Austin et al, 2004;Miao et al, 2015). Second, increased water availability may increase the capacity of plants to assimilate nitrogen by affecting the activities of nitrogen anabolism, net photosynthetic rate and/or stomatal conductance (Xu and Zhou, 2006;Habermann et al, 2019). Third, increased water availability may promote new tissues generation and delay the maturation of the plants (Schönbach et al, 2012;Ren et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments suggest that Panicum maximum (Guinea grass) would benefit by a 2˚C warming under well-watered conditions by exhibiting increased dry mass [11] and not showing increased concentration of stress indicators compounds, such as malondialdehyde and hydrogen peroxide [12]. However, under heating, there was no increase in photosynthesis and transpiration [6,13], suggesting that under a warmed atmosphere, P. maximum may exhibit increased NUE. It was also observed that under heating, P. maximum exhibited an increase in the concentration of many amino acids, such as valine, threonine and phenylalanine, which have N in their structure [14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides legal and reputational risks, the leather supply chain can also be exposed to operational risk. Increased deforestation, the feedback loop of climate change, water shortage and altered rainfall patterns is affecting the availability of resources for all industries, including cattle farming in Brazil [52,53]. and 6404) in 2018, in trade value (million USD).…”
Section: Deforestation As the Legal And Reputational Riskmentioning
confidence: 99%